AN ERROR ANALYSIS OF MODAL AUXILIARIES USAGE IN WRITING ANALYTICAL EXPOSITION TEXT (A STUDY AT THE ELEVENTH GRADE STUDENTS OF SMA NEGERI 1 ANGKOLA TIMUR 2018/2019 ACADEMIC YEAR) - PEBRITA SITOMPUL (JURNAL LINER (Language Intelligence and Educational Research), 2020)
Abstract: The aims of this research are to find out: 1). The Description of the Students’ errors in writing Analytical Exposition Text. 2). The causes of students Errors in Using Modal Auxiliaries in Writing Analytical Exposition Text. The research was conducted by using mix method (quantitative and qualitative research) with 5 students as the informants. Sample was taken by using purposive sampling. The test, interview and documentation were used in colecting data. The causes of the students errors in used modal auxiliaries in writing analytical exposition text is low interest, low disipline, lazy, lack vocabulary, low motivation, attitude and bad habbits. Furthermore, students interest was found as well in this research. The how they writing modal auxiliaries in students writing analytical exposition text from analized text students analytical exposition text, the writer found that many students are less comprehension about used of modal auxiliaries.